Minority stress and mental health in lesbian, gay male, and bisexual youths: A meta-analysis - Dürrbaum, Tina; Sattler, Frank A. (Journal of LGBT youth, 2020)
Minority stress theory proposes an increased risk of mental health problems in lesbian, gay male, and bisexual (LGB) youths. The authors conducted a meta-analysis on the relationship between minority stressors and adverse mental health outcomes in LGB youths (≤21 years). Within-group design studies published in peer-reviewed journals were included. Moderator effects of gender, age, and race as well as differences between mental health outcomes were analyzed. The aggregate correlation between minority stress and adverse mental health was r = .25, p = .001, 95% CI [.1, .38]. Implications for interventions and future research are discussed.